PEMBERDAYAAN MASYARAKAT DESA DALAM PEMANFAATAN LAYANAN DIGITAL PEMERINTAH MELALUI APLIKASI BEDAS DIGITAL SERVICE (BDS) DI DESA PANANJUNG KECAMATAN CANGKUANG KABUPATEN BANDUNG - Francisca Kristiastuti; Aty Susanti (Komunikasi, 2025)
The implementation of digital technology has brought significant changes to governance. Public service innovation through the concept of e-government represents a digital-based governance model, which is the Bedas Digital Service application. This application was designed to optimize population and civil registration administration for Kabupaten Bandung residents. The Community Service Activity by Nurtanio University Bandung is designed to educate these innovations to local government and residents of Desa Pananjung through socialization and technical support. The results of the activity indicate an increase in the understanding of both local government and residents regarding these digital-based public service innovations. The implementation of digital service in Desa Pananjung is challenged by two factors, such as limited public awareness of digital services and insufficient technical competence among digital service management. Therefore, continuous socialization and improvement of information technology competencies for local government are required to ensure the sustainability of the program.